RADIOGRAPH OF THE USE OF PIG’S BONE AS GRAFT MATERIAL TO FEMUR FRACTURE TREATMENT IN DOGS - Sudimartini, Luh Made; Wirata, I Wayan; Dharmayudha, Anak Agung Gde Oka; Gunawan, I Wayan Nico Fajar; Sudipa, Putu Henrywaesa (Buletin Veteriner Udayana, 2019)
Fracture is one of the cases that may occur in pets, especially dogs and cats. The principle to treatment cases of fracture is repositioned and immobilized in the area of ??the fracture. Large bone damage due to trauma can inhibit healing process and cause bone defects, so that graft material is needed to stimulate the healing process and to fill in the missing bone. This research was aimed to study radiographic imaging in the use of pig’s bone as graft material for the treatment of fractures in dogs. Eight male dogs aged 3-4 months were used in this study and were divided into 2 groups randomly. Group I (control) was 2 dogs who their bone diaphysis femur was drilled with a diameter of 1 cm without giving graft material. Group II was 6 dogs who were drilled as Group I and were given a graft material. Monitoring the progress of healing process by rontgent, was conducted at 24 hours, 2 nd week, 4 th week and 8 th week post-surgery. Radiographic analysis showed that there has been a unification and mineralization of bone fragments in the 8 th week post-surgery in the group II with bone density already seemed normal.